Integration of Psychological Factors and Financial Technology in Student Financial Management Models - Supami Wahyu Setiyowati; Mardiana Mardiana (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2026)
Purpose: This study examines the effects of financial literacy, self-control, and e-wallet usage on financial management, with financial attitude serving as a mediating variable. Method: A quantitative survey approach was employed to examine the causal relationships among the variables. The population consisted of 300 fourth-semester Management students at Universitas Islam Negeri Maulana Malik Ibrahim Malang in 2026 who had completed the Financial Management course. Using the Slovin formula with a 5% margin of error, 171 respondents were selected through proportionate random sampling. Primary data were collected using a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model was evaluated through validity and reliability tests, while the structural model was assessed using the coefficient of determination (R²), path coefficients, and bootstrapping. Results: The findings indicate that self-control and e-wallet usage have positive and significant effects on financial attitude. Financial attitude also has a positive and significant effect on financial management. Moreover, financial attitude mediates the relationships between self-control, e-wallet usage, and financial management, highlighting its essential role in fostering better financial management among university students. Implications: This study contributes to the financial behavior literature by integrating individual psychological factors and digital financial technology into a single mediation model. Novelty: Its novelty lies in identifying financial attitude as the underlying mechanism linking self-control and e-wallet usage to financial management, offering a more.